IDENTIFICATION AND EVALUATION OF FIBER HYDROLYTIC ENZYMES IN THE EXTRACT OF TERMITES (Glyptotermes montanus) FOR POULTRY FEED APPLICATION - Purwadari, Tresnawati; Ketaren, Pius P.; Sinurat, Arnold P.; Sutikno, Irawan (Indonesian Agency for Agricultural Research and Development - MOA, 2003)
Poultry are not able to digest fiber in the diet. Hydrolytic enzymes including cellulases and hemicellulases have been used as poultry feed supplement. Termites (Glyptotermes montanus) have the ability to digest wood that contains high fiber. The purpose of this experiment was to identify the cellulase and hemicellulase of termite extract. The hydrolytic (saccharification) activity of the termite extract on feedstuffs was thenevaluated. It contained high endo-Î²-D-1,4-glucanase (CMCase) activity, but the activities of avicelase, Î²-D-1,4-mannanase, Î²- D-1,4-xylanase, and Î²-D-1,4-glucosidase were very low. The activities of the enzymes were higher in the fresh extract than those extracted after drying at 40oC with blower oven. CMCase (as cellulase), Î²-D-1,4-mannanase (asÂ hemicellulase), and Î²-D- 1,4-glucosidase (as glycosidase) were reevaluated further to determine the optimum pH and temperatures for maximum activities. The optimum pH for CMCase, Î²-D-1,4-mannanase,and Î²-D-1,4-glucosidase were 6.2, 5.0, and 5.8 respectively, while the optimum temperatures were 45-50oC, 50-55oC, and 42-45oC, respectively. The enzyme mixture or cocktail was more appropriate in digesting feedstuffs with high lignocellulose (fiber) such as rice bran and pollard than feedstuffs with more soluble starch such as soybean and corn meals. The extracted enzyme could be immobilized with pollard, butCMCase recovery was low (28.6%), while Î²-D-1,4-mannanase and Î²-D-1,4-glucosidase recoveries were 89.2% and 272.9%, respectively. Termite extract contained enzyme cocktails of lignocellulases that potentially be used as feed supplement. However, its use is limited by its low activity.